2015
DOI: 10.1038/ejhg.2015.156
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies recessive CDK5RAP2 variants in patients with isolated agenesis of corpus callosum

Abstract: Agenesis of the corpus callosum (ACC) is a common brain malformation which can be observed either as an isolated condition or as part of numerous congenital syndromes. Therefore, cognitive and neurological involvements in patients with ACC are variable, from mild linguistic and behavioral impairments to more severe neurological deficits. To date, the underlying genetic causes of isolated ACC remains elusive and causative genes have yet to be identified. We performed exome sequencing on three acallosal siblings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Given the mild clinical phenotype and high rates of incomplete penetrance associated with DCC ‐MMs and DCC ‐iACC, cascade testing should be considered for all extended family members at risk of inheriting a mutant allele. Differential genetic diagnoses for DCC ‐MMs include NTN1 and RAD51 (MIM# 179617) (Depienne et al., ; Méneret et al., ; Méneret et al., ); for DCC ‐iACC include CDK5RAP2 (MIM# 608201, although only one family has been described to date (Jouan et al., )); and for DSBS include ROBO3 (note: individuals with HGPPS1 do not suffer from intellectual disability and have normal forebrain commissures, consistent with the predominant role of ROBO3 in the developing hindbrain and spinal cord) (Chan et al., ; Jen et al., ; Sicotte et al., ). However, the low diagnostic yield of genetic screening studies indicates that additional MMs and iACC disease genes remain to be identified and therefore mutations in DCC , NTN1 , RAD51 , and CDK5RAP2 will not always be identified in individuals with these phenotypes (Franz et al., ; Jamuar et al., ; Marsh et al., ; Méneret et al., ; Méneret et al., ; Méneret, et al., ).…”
Section: Diagnostic Strategiesmentioning
confidence: 96%
“…Given the mild clinical phenotype and high rates of incomplete penetrance associated with DCC ‐MMs and DCC ‐iACC, cascade testing should be considered for all extended family members at risk of inheriting a mutant allele. Differential genetic diagnoses for DCC ‐MMs include NTN1 and RAD51 (MIM# 179617) (Depienne et al., ; Méneret et al., ; Méneret et al., ); for DCC ‐iACC include CDK5RAP2 (MIM# 608201, although only one family has been described to date (Jouan et al., )); and for DSBS include ROBO3 (note: individuals with HGPPS1 do not suffer from intellectual disability and have normal forebrain commissures, consistent with the predominant role of ROBO3 in the developing hindbrain and spinal cord) (Chan et al., ; Jen et al., ; Sicotte et al., ). However, the low diagnostic yield of genetic screening studies indicates that additional MMs and iACC disease genes remain to be identified and therefore mutations in DCC , NTN1 , RAD51 , and CDK5RAP2 will not always be identified in individuals with these phenotypes (Franz et al., ; Jamuar et al., ; Marsh et al., ; Méneret et al., ; Méneret et al., ; Méneret, et al., ).…”
Section: Diagnostic Strategiesmentioning
confidence: 96%
“…All diseases associated with primary (congenital) microcephaly without further extracranial malformations and without facial dysmorphism are included in the differential diagnosis of MCPH. Phenotyping and genotyping of patients with overlapping but seemingly distinct phenotypes has revealed a phenotype and genotype overlap with isolated agenesis of the corpus callosum (ACC), 39 Seckel's syndrome (microcephalic dwarfism type I), 13,14,40 and microcephalic osteoplastic dwarfism type II (MOPDII) 41 (►Fig. 4).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In addition to severe microcephaly, other clinical features of MCPH3 include mild to moderate mental retardation, developmental delay, small but structurally normal cerebral cortex, seizures, sloping forehead, and sensorineural hearing loss. Furthermore, homozygous and compound heterozygous variants in CDK5RAP2 has been reported in affected children with Seckel syndrome (Yigit et al., ) and isolated agenesis of corpus callosum (Jouan et al., ).…”
Section: Introductionmentioning
confidence: 99%